Growth inhibition of nematophagous and entomopathogenic fungi by leaf litter and soil containing phenols - Lopez-Llorca, L. V.; Olivares-Bernabeu, C. (Mycological Research, 1997)
In a soil survey, nematophagous fungi were recovered less from agar plates sprinkled with forest soil (Quercus ilex subsp. rotundifolia) than from those incubated with agricultural (Citrus orchards) soil. Nematodes were present in all soils. The organic matter was higher in forest soils. Water extracts from forest soils with high levels of phenols, leaf litter and Q. rotundifolia fresh leaves aﬀected the development and growth of common species of nematophagous and entomopathogenic fungi. These results show that phenolics from leaf letter could play an important role in the ecology and biology of these invertebrate pathogens in soil.
Keywords: agricultural soil; entomopathogenic fungi; forest soil; fungal growth (voyant); leaf litter; nematophagous fungi; phenolic compounds; quercus ilex ssp rotundifolia

Growth inhibition of nematophagous and entomopathogenic fungi by leaf litter and soil containing phenols - Lopez-Llorca, L V; Olivares-Bernabeu, C (Mycological Research, 1997)
In a soil survey, nematophagous fungi were recovered less from agar plates sprinkled with forest soil (Quercus ilex subsp. rotundifolia) than from those incubated with agricultural (Citrus orchards) soil. Nematodes were present in all soils. The organic matter was higher in forest soils. Water extracts from forest soils with high levels of phenols, leaf litter and Q. rotundifolia fresh leaves aﬀected the development and growth of common species of nematophagous and entomopathogenic fungi. These results show that phenolics from leaf letter could play an important role in the ecology and biology of these invertebrate pathogens in soil.
Keywords: agricultural soil; entomopathogenic fungi; forest soil; fungal growth (voyant); leaf litter; nematophagous fungi; phenolic compounds; quercus ilex ssp rotundifolia

Effects of fire on soil carbon and nitrogen in a Mediterranean oak forest of Algeria - Rashid, G H (Plant and Soil, 1987)
The effects of wildfire on the dynamics of pH, organic C, total and mineral N and in vitro C and N mineralization were investigated in the soil under oak (Quercus suber L.) trees. Soil samples were taken from 5 to 21 months subsequent to the fire. The pH increased sharply in the burned surface soil (0-5 cm) taken 5 months after the fire and dropped only by half a unit over 14 to 21 months. However, at greater depth (5-15 cm), the burned soil was more acidic than the adjacent unburned soil up to 9 months following the fire, and thereafter its pH rose only slightly above that of the unburned soil. There were sharp rises in the concentration of organic C, total and mineral N in addition to in vitro mineralization activities in the burned surface soil collected 5 months after the fire; these dropped off in the subsequent samples approaching or falling below the values obtained in the unburned surface soil after 21 months. At a depth of 5-15 cm only slight or no increases over unburned soil were evident.
Keywords: Carbon; forest soil; mineralization; nitrogen; pH; Wildfire